The Role of Manufacturing Industrial Activity in the Environmental Pollution in South Sulawesi - Astuti, Tri (Journal of Economics and Behavioral Studies, 2015)
Deteriorating environmental conditions can be a hindrance in creating a sustainable economic development so that necessary concern of all parties. The study aims to identify the industrial sectors causing the heaviest pollution and to confirm the environmental economic theories applicable to the condition in South Sulawesi. The study objects are the economic activities in South Sulawesi as summarized in the I-O table transactions. The data used are secondary data of the income per capita and of environmental pollution, table I-O of South Sulawesi in 2010, and the IPPS standard of pollution intensity estimate, and cost coefficient for pollution eradication. The tools used are conventional input-output, environmental input-output, and trend analyses. The reveals that the chemical and metal manufacturing industry sectors are the primary causes of severe pollution in South Sulawesi in 2010 and the environmental economic cases tend to comply with Hypothesis Haven. This research is an academic study limited only to investigate the role of economic activities in industrial manufacturing sector so that further study can be foccused on the role of the whole activities of the economic sector in the environmental pollution.